Investigating the racial gap in prostate cancer screening with prostate-specific antigen among younger men from 2012 to 2020. Issue 2 (27th January 2023) - Qian, Zhiyu; Al Khatib, Khalid; Chen, Xi; Belani, Sanvi; Labban, Muhieddine; Lipsitz, Stuart; Cole, Alexander P; Iyer, Hari S; Trinh, Quoc-Dien
Abstract: Background: The United States Preventive Services Task Force recommended against prostate-specific antigen (PSA) screening in 2012, which was modified in 2018 into shared decision making for men aged 55-70 years with a life expectancy over 10 years. We studied the trends in PSA screening in younger Black and White men with the implementation of the 2012 and 2018 guidelines. Methods: Younger Black and White men (aged 40-54 years) were identified using the Behavioral Risk Factor Surveillance System database biennially from 2012 to 2020. Our primary outcome was PSA screening within 2 years of the survey. An adjusted logistic regression model with 2-way interaction assessment between race and survey year was used to investigate the temporal trend of PSA screening in younger Black and White men. Results: A total of 142 892 men were included. We saw steadily decreasing odds of PSA screening among both younger Black and White men in 2014, 2016, 2018, and 2020 compared with 2012 (for younger Black men: odds ratio [OR]2014 = 0.77, 95% confidence interval [CI] = 0.62 to 0.96, OR2016 = 0.51, 95% CI = 0.41 to 0.63, OR2018 = 0.33, 95%CI = 0.27 to 0.42, OR2020 = 0.25, 95% CI = 0.18 to 0.32; and for younger White men: OR2014 = 0.81, 95% CI = 0.76 to 0.87, OR2016 = 0.66, 95% CI = 0.61 to 0.71, OR2018 = 0.41, 95%CI = 0.37 to 0.44, OR2020 = 0.36, 95% CI = 0.33 to 0.39). Younger Black men showed a brisker decrease in PSA screening in 2016, 2018, and 2020 compared with younger White men (all P < .05). Conclusions: PSA screening among younger men steadily decreased over the past decade since the 2012 United States Preventive Services Task Force guidelines, demonstrating a narrowing racial gap. How such an observed trend translates to long-term clinical outcomes for younger Black men remains to be seen.